An Efficient Portfolio Management for Trading Under Uncertain Environment - Pritam, Kocherlakota Satya; Mathur, Trilok; Agarwal, Shivi (ExcelingTech, 2019)
This study presents a framework for efficient portfolio management for trading under uncertain environment. The proposed framework can be used to determine the dominance of various sectors among the chosen set of alternatives. The dominance of these sectors are analyzed by considering various aspects such as Return on equity, Book value per share, Price earnings ratio, and Price to book ratio. For illustration, the dominance of various sectors is evaluated using the proposed framework. The historical stats of various sectors, corresponding to the aforementioned criteria's are collected from various sources and the dominance is studied using the proposed framework. The findings of this study facilitate novice users in understanding the relative dominance of each sector.